The Association Between Antenatal Maternal Self-reported Substance Use, Maternal Characteristics, and Obstetrical Variables. Issue 6 (November 2019) - Berra, Alexandra; Kamo, Shota; Mohnot, Sopan; Rosselot, Jessica; Suire, Andrew; Stafford, Joshua; Hagan, Joseph; Stafford, Irene
Abstract : Background: Substance use disorders during pregnancy are a concern both to the public and medical community, because the negative consequences can be detrimental to both mother and the fetus. The accurate identification of prenatal drug exposure is necessary to determine appropriate medical and psychosocial intervention, and to identify risk factors that may affect outcomes for the mother and her newborn. The prevalence of prenatal drug exposure is very difficult to estimate because of flaws in all methods of identification. Objective: The study is designed to identify risk factors and demographic variables that contribute to nondisclosure of illicit and nonillicit substance use. In addition, this study aims to determine if nondisclosure leads to adverse neonatal outcomes. Study design: Newborns delivered with a positive meconium or urine toxicology, and/or known maternal exposure to illicit and nonillicit substances, were identified. Maternal records were reviewed for disclosure of substance use during pregnancy at admission for delivery along with other medical and demographic variables. Women with antenatal prescription drug use that may alter toxicology screens were excluded from analysis. Pediatric records were also reviewed to obtain neonatal variables. Results: One hundred sixty-eight newborns were identified as having prenatal exposure to an illicit or nonillicit substance over the 4-year period. Eighty-six per cent (145/168) of women tested positive or their newborn tested positive for at least 1 illicit substance, and 49% (82/168) tested positive for multiple illicit substances. Fifty-four per cent (91/168) of women did not disclose using at least one illicit drug for which she or her newborn tested positive. With regards to maternal characteristics, there was no statistically significant difference between age ( P  = 0.958), parity ( P  = 0.300), or race ( P  = 0.531), and disclosure or failure to disclose about illicit drug use. However, patients who did not report prenatal illicit drug use (33/82 = 40%) were less likely ( P  = 0.049) to receive complete prenatal care (defined as 3 or more visits) compared with those who acknowledged their substance use (40/70 = 57%). Conclusion: Substance use disorders during pregnancy are an often underestimated cause of maternal, fetal, and neonatal complications. Limited studies have examined the relationship between maternal characteristics and associated illicit or nonillicit drug use. The absence of correlation between maternal demographics and disclosure of illicit substance use demonstrates the fact that all antepartum patients are at risk for these behaviors. Furthermore, the fact that women who did not disclose their illicit drug use were less likely to seek complete prenatal care reflects the need for physicians to provide a destigmatized healthcare environment, encouraging pregnant women to disclose their substance use so they can be provided with appropriate counseling and treatment.